2016
DOI: 10.1111/jdv.13839
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic clinical factors associated with remission and relapse in bullous pemphigoid

Abstract: This study suggests BP patients who are older and have no admission history tend to achieve remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Negative reaction to BP180 and BP230 ELISA might be a predictive sign of non-relapse. Overall, our study contained a small number of samples, although the frequency of relapse (34%) in our study was similar to that reported previously in Europe ( 12 , 13 ) and Asia ( 24 ). Therefore, further study with larger sample sizes will be required.…”
Section: Discussionsupporting
confidence: 87%
“…Negative reaction to BP180 and BP230 ELISA might be a predictive sign of non-relapse. Overall, our study contained a small number of samples, although the frequency of relapse (34%) in our study was similar to that reported previously in Europe ( 12 , 13 ) and Asia ( 24 ). Therefore, further study with larger sample sizes will be required.…”
Section: Discussionsupporting
confidence: 87%
“…Among BP patients, 73.8-85% were reported to be treated with systemic corticosteroid [15][16][17] and relapse rates were reported to be 15-53%. 3,5,[18][19][20][21][22][23] This clearly contrasts with pemphigus patients; we recently reported that 62% of pemphigus patients experienced relapse at least once and all of them had been treated with oral PSL. 24 In Japanese guidelines for pemphigoid management, oral PSL (0.5-1 mg/kg) is recommended as a first-line treatment for moderate to severe BP.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, 37.2% of patients were treated without oral PSL and the relapse rate was less than 10% in those patients (Tables 1 and 4). Among BP patients, 73.8–85% were reported to be treated with systemic corticosteroid 15–17 and relapse rates were reported to be 15–53% 3,5,18–23 . This clearly contrasts with pemphigus patients; we recently reported that 62% of pemphigus patients experienced relapse at least once and all of them had been treated with oral PSL 24 …”
Section: Discussionmentioning
confidence: 99%